Bridging neoliberalism and Hindu nationalism : the role of education in bringing about contemporary India - Lall, M. C. (Marie-Carine); Anand, Kusha (Bristol University Press, 2022)
Hindu Nationalism is not well understood outside of India, and its links to the global neoliberal trajectory have not been much explored. This important book shows why it is education, not a failed political system, that led to the rise of Modi and the right-wing nationalist ideology of Hindutva.